The origin of gastric cancer stem cells and their effects on gastric cancer: Novel therapeutic targets for gastric cancer - Yang, Ying; Meng, Wen-Jian; Wang, Zi-Qiang (Frontiers in Oncology, 2022)
Gastric cancer (GC) is one of the most prevalent malignancies and the most common causes of cancer-related mortality worldwide. Furthermore, the prognosis of advanced GC remains poor even after surgery combined with chemoradiotherapy. As a small group of cells with unlimited differentiation and self-renewal ability in GC, accumulating evidence shows that GC stem cells (GCSCs) are closely associated with the refractory characteristics of GC, such as drug resistance, recurrence, and metastasis. With the extensive development of research on GCSCs, GCSCs seem to be promising therapeutic targets for GC. However, the relationship between GCSCs and GC is profound and intricate, and its mechanism of action is still under exploration. In this review, we elaborate on the source and key concepts of GCSCs, systematically summarize the role of GCSCs in GC and their underlying mechanisms. Finally, we review the latest information available on the treatment of GC by targeting GCSCs. Thus, this article may provide a theoretical basis for the future development of the novel targets based on GCSCs for the treatment of GC.